Archäologische Geländebegehungen - Pfälzner, P.
ersch. 1985; P. Pfälzner, Wadi Aǧīǧ; K. Simpson, Tall al-‘Ashārah; P. M. M. G. Akkermans, Baliḫ-Tal; K. Kohlmeyer, Euphrat-Tal; F. Braemer, Ḥawrān; M. Moussli, Tall Ramzūn.